Conditional deletion of WT1 in the septum transversum mesenchyme causes congenital diaphragmatic hernia in mice - Carmona-Mejías, Rita María; Cañete, A; Cano, E; Ariza, L; Rojas, A; Muñoz-Chápuli, R (Elife, 2016)
Congenital diaphragmatic hernia (CDH) is a severe birth defect. Wt1-null mouse embryos develop CDH but the mechanisms regulated by WT1 are unknown. We have generated a murine model with conditional deletion of WT1 in the lateral plate mesoderm, using the G2 enhancer of the Gata4 gene as a driver. 80% of G2-Gata4(Cre);Wt1(fl/fl) embryos developed typical Bochdalek-type CDH. We show that the posthepatic mesenchymal plate coelomic epithelium gives rise to a mesenchyme that populates the pleuroperitoneal folds isolating the pleural cavities before the migration of the somitic myoblasts. This process fails when Wt1 is deleted from this area. Mutant embryos show Raldh2 downregulation in the lateral mesoderm, but not in the intermediate mesoderm. The mutant phenotype was partially rescued by retinoic acid treatment of the pregnant females. Replacement of intermediate by lateral mesoderm recapitulates the evolutionary origin of the diaphragm in mammals. CDH might thus be viewed as an evolutionary atavism.
Keywords: Hernia diafragmática; Gata4; wilm's tumor suppresor gene; congenital diaphragmatic hernia; developmental biology; epithelial-mesenchymal transition; human biology; medicine; mouse; stem cells